VISUAL AUDITORY KINESTHETIC METHOD IN KRUMP HIP-HOP DANCE AT ROSSY'S STUDIO: Metode Visual Auditory Kinesthetic Pada Krump Hip-Hop Dance di Sanggar Rossy’s - Listianingsih, Ratu; Alis Triena Permanasari; Dwi Juniarti Lestari (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
In teaching and learning activities in the scope of non-formal education, a teacher must understand and must be able to provide encouragement so that students have a rapid interest in practical activities in studying dance. Not a few non-formal education units are less able to provide understanding and methods in learning interesting practices, so a comprehensive solution lies in the teaching system in managing a scope that makes it an effective and comfortable place both from the perspective of strategies, models and methods in carrying out learning. The discussion of the research refers to the implementation of methods in dance learning. The learning method is a method that is differentiated by adjusting the needs of students, namely visual, auditory and kinesthetic. This method is associated with krump-style hip-hop dance. The learning includes how to learn and techniques on the dance learning material. This research approach is qualitative on the basis of descriptive methods with data collection techniques of observation, interviews and document studies.